2020
DOI: 10.1088/1742-6596/1595/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Fe3O4concentration to photocatalytic activity of Fe3O4@TiO2-PVP core-shell nanocomposite

Abstract: A study on the preparation of Congo red textile dyes using nanocatalysts, Fe3O4@TiO2 material, and Polyvinyl Pyrrolidone (PVP) has been successfully carried out. The preparation of these dyes is intended as a controller of the shape and size of particles and as a superior adhesive in solution. Fe3O4@TiO2 core-shell (FTP) nanocomposite was carried out by coprecipitation method. The Fe3O4 nanoparticles were designed as cores that were synthesized from Cilacap iron sand, while TiO2 nanoparticles were selected as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The magnetic properties of these nanoparticles and their modifications have also led these materials to selectively accumulate at the tumor site through externally directed magnetic force. Thus, the delivery is considered “targeted” [ 24 ]. However, the easy agglomeration of the IONPs has curtailed their utility, and several frontline applications and biomedical approaches of the IONPs have been hindered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetic properties of these nanoparticles and their modifications have also led these materials to selectively accumulate at the tumor site through externally directed magnetic force. Thus, the delivery is considered “targeted” [ 24 ]. However, the easy agglomeration of the IONPs has curtailed their utility, and several frontline applications and biomedical approaches of the IONPs have been hindered.…”
Section: Introductionmentioning
confidence: 99%
“…The making of the core-shell iron oxide-titania NPs by TiO 2 insertion as the core of the core-shell through following an independent synthetic approach has provided an option in finding metal-based site-specificity to the tumor location, especially the biosystems deep-located and embedded cancers. The core-shell nanocomposite structures are known to increase the composite NPs stability and provide enhanced dispensability, together with magnetically driven delivery and heat generation at the site [ 24 , 25 ]. The characteristics and requirements have placed the core-shell materials as a potential target for further investigations.…”
Section: Introductionmentioning
confidence: 99%
“…13a. Based on the experimental results and analytical studies described above, a possible electron-hole transfer mechanism can be explained as follows: The defective crystal structure of the PPS/PVA/Fe 3 O 4 nanocomposite increases the light sensitivity and offers an e cient visible light harvesting capability [19,41]. The magnetic nanocomposite absorbs light photons whose wavelengths are equal to or greater than its bandgap (Eg).…”
Section: Possible Photocatalytic Mechanismmentioning
confidence: 99%
“…It has good chemical stability, exibility, inherent ame resistance, and superb mechanical and environmental properties [16]. Despite its electrical insulation characteristics, high-performance PPS is used as a host matrix of composites, and many studies have revealed its successful employment in photocatalysis to boost photocatalytic activity [8,11,[17][18][19]. The PPS backbone has plenty of benzene rings, forming π-π stacking adsorption and acting as electron sources for electrophilic substitution reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation